TWIN FORMATION AND STRUCTURAL MODULATIONS IN ORTHORHOMBIC AND TETRAGONAL YBA2(CU1-XCOX)3O7-DELTA - Schmahl, W; Putnis, A; Salje, E; Freeman, P; Graemebarber, A; Jones, R; Singh, K; Blunt, J; Edwards, P; Loram, J; Mirza, K (1989)
The microstructure of YBa2(Cu1-xCox)3O7-δ, prepared by the standard ceramic method, shows lamellar twin structures with decreasing spacings between twin walls with increasing Co content for x≲0.02, developing into {110}-type cross-hatched 'tweed' modulation for x≳0.02. Several wall junctions are found for x=0.02. The structural phase transition between macroscopically orthorhombic and tetragonal material occurs at x≈0.025; structural modulations (λ≈20 angstrom) persist in the samples with high Co content (x>0.25). The modulations lead to a considerable broadening of the X-ray lines affected by orthorhombic splitting and show maximum amplitude at the critical composition x≈0.025.